Trajectories of family functioning and financial toxicity in patients with glioma: a longitudinal study - Yue Wu; Yihao Wu; Botao Zhou; Yongmou Sun; Rufei Dai (Frontiers in Public Health)
ObjectiveThis study aims to investigate the longitudinal trajectories of family functioning and financial toxicity in glioma patients, while examining their predictive interrelationships, to establish evidence-based strategies for alleviating economic burden in neuro-oncology care.MethodsThis prospective longitudinal cohort study enrolled 266 glioma patients from the Second Affiliated Hospital of Xuzhou Medical University and Xuzhou Central Hospital (January 2022–June 2024). Family functioning and financial toxicity were serially assessed at three timepoints: baseline (T1, initial diagnosis), 3-month follow-up (T2), and 6-month follow-up (T3). Structural equation modeling (SEM) framework incorporated cross-lagged panel analysis and latent growth curve modeling to examine temporal relationships.ResultsA total of 242 valid consecutive questionnaires were collected. The cross-lagged panel analysis demonstrated that the average family functioning level significantly and positively predicted subsequent financial toxicity at follow-up time points (β = 0.478, p = 0.01; β = 0.463, p < 0.001), while financial toxicity exhibited no significant longitudinal predictive effect on family functioning across subsequent assessments. The latent growth curve modeling revealed parallel declining trajectories: family functioning (slope [S] = −0.410, p < 0.001) and financial toxicity (slope [S] = −0.102, p < 0.001) both decreased significantly from T1 to T3. At baseline, family functioning showed positive correlation with financial toxicity scores (r = 0.377, p = 0.002). Initial family functioning level demonstrated dual regulatory effects: (1) negative auto-regulation (β = −0.352, p = 0.007) and (2) inverse prediction of financial toxicity’s developmental trajectory (β = −0.516, p = 0.002). Crucially, the initial family functioning level exhibited compensatory effects on financial toxicity dynamics, showing negative coupling with its growth rate (β = −0.534, p < 0.001).ConclusionFamily functioning and financial toxicity of glioma patients can predict each other. The initial level of family functioning can positively predict the initial level of financial toxicity, the initial level of family functioning can negatively predict the development speed of itself and financial toxicity, and the development speed of family functioning can positively predict the development speed of financial toxicity.